Sobre a prudência infusa em Tomás de Aquino: uma leitura a partir da Ética a Nicômaco de Aristóteles - Cigognini, Enir (2018)
The present thesis work investigates the issue of the infused prudence virtue in the Saint Thomas Aquinas’ Treaty of Prudence. The main question to answer is how author of Summa Theologiae affirms in the Treaty of Virtues the virtue of infused practical wisdom and in dealing with prudence abandons this concept. The research seeks to show like virtue can be produced in the human being, according to the thought of Thomas Aquinas, and, using the historical context in which the author lives, the chronology of his works and the thesis sustained by Alasdair MacIntyre, demonstrates that the concept of infused prudence is abandoned due to a dominant Aristotelian influence present in De Prudentia.